2022
DOI: 10.1007/s12144-022-03976-1
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemial babies: effects of maternal stress on temperament of babies gestated and born during the pandemic

Abstract: The COVID-19 pandemic may configure an adverse prenatal context for early development. The aim of this study was to analyze the effects of pandemic-related negative experiences, prenatal anxiety and depression on the temperament of six-month-old babies. The sample consisted of 105 mother–child dyads. A longitudinal evaluation was carried out using pre- and postnatal online surveys. Mothers completed the State-Trait Anxiety Inventory, the Beck Depression Inventory – II, the Pandemic Impact Questionnaire and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
4
2
Order By: Relevance
“…Only a few known studies have examined mechanisms linking prenatal pandemic-related stress with infant temperament (López- Morales et al, 2022;Sacchi et al, 2023). In contrast to the present findings, López- Morales et al (2022) found prenatal pandemic stress indirectly predicted infant negative affect and surgency at 6 months through prenatal anxiety rather than depression symptoms during pregnancy.…”
Section: Pandemic-related Stress and Temperamentcontrasting
confidence: 99%
See 3 more Smart Citations
“…Only a few known studies have examined mechanisms linking prenatal pandemic-related stress with infant temperament (López- Morales et al, 2022;Sacchi et al, 2023). In contrast to the present findings, López- Morales et al (2022) found prenatal pandemic stress indirectly predicted infant negative affect and surgency at 6 months through prenatal anxiety rather than depression symptoms during pregnancy.…”
Section: Pandemic-related Stress and Temperamentcontrasting
confidence: 99%
“…Only a few known studies have examined mechanisms linking prenatal pandemic-related stress with infant temperament (López- Morales et al, 2022;Sacchi et al, 2023). In contrast to the present findings, López- Morales et al (2022) found prenatal pandemic stress indirectly predicted infant negative affect and surgency at 6 months through prenatal anxiety rather than depression symptoms during pregnancy. Of note, these researchers utilized a COVID-19 measure that identified whether women were exposed to a series of stressful events during the pandemic, whereas the current study evaluated perceived stress related to perinatal infection and preparing for their baby's arrival.…”
Section: Pandemic-related Stress and Temperamentcontrasting
confidence: 99%
See 2 more Smart Citations
“…Evidence from pregnant cohorts around the world suggests that women experienced elevated symptoms of stress, anxiety and depression during the COVID-19 pandemic [5][6][7][8]. Furthermore, early reports indicate that antenatal exposure to maternal pandemic-related stress (PRS) is associated with early infants' developmental outcomes, including temperament [9][10][11][12], socio-emotional development [13], motor outcomes [14] and even brain connectivity patterns [15].…”
Section: Introductionmentioning
confidence: 99%